Advocacy for an integrative approach in psychopathology - BENAMSILI , Lamia (Journal of Human Sciences, 2020)
The purpose of this article is to advocate for an integrative approach to psychic disorders. After a brief review of the notion of a theoretical model, its functions and its sources, the author raises the issue of the heterogeneity of approaches in psychopathology and pleads for an integrative perspective of the human psychic functioning, normal and pathological.